Королева-пугало - Солсбери Мелинда (Young Adult. Фэнтези. Дочь Пожирательницы Грехов, 2018)
Экземпляры: аб. (2023) / Инвентарный номер: 59404 / Цена: / Сис.шифр: 84(4Вел) / Авт.знак: С 60 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44